(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Major depressive disorder (MDD) is a chronic and recurrent psychiatric illness that represents one of the leading causes of disability and reduced quality of life worldwide. Pharmacotherapy remains a cornerstone of MDD management, with selective serotonin reuptake inhibitors (SSRIs) and serotonin–norepinephrine reuptake inhibitors (SNRIs) recommended as first-line agents due to their proven efficacy and overall safety. Comparative evidence evaluating both effectiveness and tolerability is therefore essential to guide rational antidepressant selection in routine clinical practice. Objective: To compare the effectiveness and tolerability of duloxetine, sertraline, and escitalopram in adults with MDD. Methods: This was a 12-week, randomized, open-label, parallel-group study conducted among adult outpatients meeting DSM-5 diagnostic criteria for MDD. A total of 90 patients were enrolled and randomly allocated into three treatment groups (n = 30 each). Group A received duloxetine at doses ranging from 30 to 60 mg/day, Group B received sertraline 50 to 100 mg/day, and Group C received escitalopram 10 to 20 mg/day, with dose titration based on clinical response and tolerability. The primary efficacy outcome was change in depressive symptom severity measured using the 17-item Hamilton Depression Rating Scale (HDRS), assessed at baseline and at weeks 4, 8, and 12. Tolerability and safety were evaluated. Results: All three treatment groups demonstrated significant improvement in depressive symptoms. Within-group analysis revealed a statistically significant reduction in HDRS scores from baseline in all groups (p < 0.001). The mean reduction in HDRS score was numerically greatest in the duloxetine group (14.8 ± 5.1), followed by the escitalopram group (13.2 ± 4.7) and the sertraline group (12.5 ± 5.3). However, between-group comparisons did not show a statistically significant difference in antidepressant efficacy (p = 0.21), indicating comparable effectiveness among the three drugs. With regard to tolerability, escitalopram was associated with the lowest incidence of adverse events. Conclusion: Duloxetine, sertraline, and escitalopram demonstrated comparable effectiveness in reducing depressive symptoms over a 12-week treatment period in adults with MDD. While efficacy outcomes were similar, escitalopram exhibited a modest advantage in tolerability, suggesting it may be better suited for patients who are sensitive to adverse effects.